Improving software development process in public institutions in Peru applying COSMIC method: case study in the OSINFOR - Marca Quispe, Raul (2023)
One of the main challenges when managing software projects is determining the effort needed to deliver the product, and in Peru, public entities are aligned in regulatory compliance, which is why the use of agile approaches has increased due to the uncertainty in measuring the size of the software. In that sense, through this research, the development process for OSINFOR was improved by incorporating the COSMIC method to measure the software size and determine the effort for developments. The improved process has been analyzed in two case studies to corroborate the standard measurement and approximation approach from COSMIC method. Finally, as a result, it has been shown that the incorporation of measurement activities considering the COSMIC standard improves the process for building software, achieving 75% in compliance with the activities, 75% in the measurement efficiency and 76% in the satisfaction with the use of the improved process.